1996
DOI: 10.1063/1.871681
|View full text |Cite
|
Sign up to set email alerts
|

The dynamics of marginality and self-organized criticality as a paradigm for turbulent transport

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
193
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 222 publications
(206 citation statements)
references
References 14 publications
13
193
0
Order By: Relevance
“…It is difficult to understand how a dynamical system containing a strongly turbulent key component can ex-hibit indications of low dimensional behavior. But Chang (1992Chang ( , 1998Chang ( , 1999 has shown that this is exactly the behavior to be expected from a system in self-organization and studies of turbulent transport in magnetically confined plasmas have confirmed this (Diamond and Hahm, 1995;Newman et al, 1996;Carreras et al, 1996).…”
Section: Complexity In the Magnetospherementioning
confidence: 76%
“…It is difficult to understand how a dynamical system containing a strongly turbulent key component can ex-hibit indications of low dimensional behavior. But Chang (1992Chang ( , 1998Chang ( , 1999 has shown that this is exactly the behavior to be expected from a system in self-organization and studies of turbulent transport in magnetically confined plasmas have confirmed this (Diamond and Hahm, 1995;Newman et al, 1996;Carreras et al, 1996).…”
Section: Complexity In the Magnetospherementioning
confidence: 76%
“…Consequently, for weakly unstable states, the problem of studying the dynamics of our model consists in finding an approximate equation for the dynamics of U, E and N being determined at the end of the day from the slaving conditions (20), (18). The form of the reduced equation for U is quite different for µ 1 = 0 and µ 1 = 0.…”
Section: Dynamics Near Marginal Stabilitymentioning
confidence: 99%
“…For the same reason, the range of plasma parameters considered is not yet in an L-mode regime. Therefore, we do not expect avalanche-like transport [19,20] and the transport terms can be represented by purely diffusive terms. Concretely, we discuss an extension to 1-D of the original model used in comparison with the experimental data [11].…”
Section: Introductionmentioning
confidence: 99%
“…SGT has wide applicability [5,6] including type III solar radio bursts [5], magnetospheric Langmuir, beam and z-mode waves [7], and pulsar emissions [8], plus a range of quasilinear, particle-in-cell, and other simulations [6]. Evidence for other statistical plasma theories, such as SOC, has been found in solar flares and the intermittent turbulence of the Earth's magnetotail [9][10][11] and it has been invoked to describe confinement and transport phenomena in magnetically confined plasmas [12,13].These successes motivate searching for new applications of statistical plasma theories. In this Letter we perform a statistical analysis of fluctuations in a laboratory plasma and find lognormal distributions over a wide range of field strength, the first laboratory evidence for an SGT state.…”
mentioning
confidence: 99%